Drip irrigation system for orchard trees in Malaysia - M. Soom, Amin (1982)
The high annual rainfall of Malaysia is unevenly distributed throughout the year. Supplemental irrigation will be beneficial for good yields and quality of crops. The water saving feature of drip irrigation system warrants adoption of the system on some soils and crops in Malaysia. Marginal land such as bris soils and tin-tailings may be developed for productive agriculture by installing a drip irrigation system to-supply moisture, especially during the critical growth stage of the crops. This paper presents drip irrigation system design using drilled holes as emitters. Discharge calibration on 1 mm diameter drilled hole is given. The use of drilled holes instead of commercial emitters reduces system cost, and a less expensive system would-make drip irrigation more attractive to potential users.